Email System for Disabled - Meenu , Sushil Malik, Swati Arora , (International Journal of Scientific Research and Management (IJSRM), 2017)
Email System for Disabled is an application for the disabled people. The disabled people particularly mean the handicapped orthe blind people who cannot type on the keyboard. This application is aimed at helping such people to compose and retrieve their emails bythemselves. Voice operatability has been implemented to achieve this objective. The Disabled speaker will verbally speak the message tobe composed and then the message will be converted to text and will be embedded in the body of the e-mail. Thus, Voice-to-texttechnique can help a disabled student to type his e-mail on his own. The sent mail will be retrieved and all the unread messages will be readfor the Disabled user. The text-to-voice technique is being used here.